2020
DOI: 10.1038/s41598-020-57637-z
|View full text |Cite
|
Sign up to set email alerts
|

HBV X protein mutations affect HBV transcription and association of histone-modifying enzymes with covalently closed circular DNA

Abstract: The hepatitis B X protein (HBx) plays a role in the epigenetic regulation of hepatitis B virus (HBV) replication. This study investigated the effects of HBx mutations on HBV transcription and the recruitment of HBx, histone acetyl-transferase P300 and histone deacetylase 1 (HDAC1) to circularized HBV DNA (which resembles covalently closed circular DNA [cccDNA]). Compared with wild type, majority of mutants had lower levels of intracellular HBV RNA (44-77% reduction) and secretory HBsAg (25-81% reduction), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The vectors (pcDNA3.1 and pCR-Blunt II-TOPO) were purchased from Thermo Fisher Scientific. The HBx expression plasmid (pHBx) was constructed as previously reported 46 . SIRT4 plasmid provided by Mammalian Gene Collection (MGC:130046) was obtained from PlasmID Repository at Harvard Medical School.…”
Section: Methodsmentioning
confidence: 99%
“…The vectors (pcDNA3.1 and pCR-Blunt II-TOPO) were purchased from Thermo Fisher Scientific. The HBx expression plasmid (pHBx) was constructed as previously reported 46 . SIRT4 plasmid provided by Mammalian Gene Collection (MGC:130046) was obtained from PlasmID Repository at Harvard Medical School.…”
Section: Methodsmentioning
confidence: 99%
“…54 A number of cccDNA-associated proteins, including the hepatitis B core and X proteins (HBc and HBx, respectively), transcription factors such as cAMP response element binding protein (CREB), signal transcription factors 1 and 2, chromatin modification proteins such as histone deacetylase 1, p300/CREB-binding protein, protein arginine methyltransferase 1 and 5, and sirtuin 1, have been demonstrated to regulate the transcriptional activity of HBV. 52,[54][55][56][57][58][59][60][61] In theory, these cellular and viral epigenetic factors can facilitate a robust control of viral replication, leading to very low HBV DNA and undetectable HBsAg in patients with OBI. 62 However, to date, direct evidence of the involvement of these epigenetic factors in OBI has yet to be reported.…”
Section: Virology Epigenetics and Immunology Of Obimentioning
confidence: 99%
“…68 However, partly due to the scarcity of adequate animal or in vitro models for OBI study, current data have, by necessity, been based on inferences generated from experiments designed to control HBV replication using in vitro systems approximating CHB infection. [54][55][56][57][58][59][60][61] Association of OBI and HCC Woodchuck model of OBI The woodchuck model of OBI is an excellent experimental system to study the pathogenicity of occult hepadnaviral persistence and its role in the development of HCC. 69 Investigators reported that woodchucks infected with low doses of WHV developed asymptomatic, seronegative, molecularly evident persistent occult hepatitis with a low viral load.…”
Section: Key Pointmentioning
confidence: 99%
“…In the case of HBx-minus HBV mutants, histones are hypoacetylated, while the recruitment of histone deacetylases histone deacetylase 1 (HDAC1) and sirtuin-1 (SIRT1) are profoundly increased [61]. Furthermore, mapping analysis determined that C-terminally mutated HBx recruits less acetyltransferase p300 and more HDAC1 onto cccDNA templates [83]. HBx not only initiates but also maintains transcription from cccDNA.…”
Section: Host and Viral Mediators Of Hbv Transcriptionmentioning
confidence: 99%